2014
DOI: 10.14411/eje.2014.024
|View full text |Cite
|
Sign up to set email alerts
|

A goodbye letter to alcohol: An alternative method for field preservation of arthropod specimens and DNA suitable for mass collecting methods

Abstract: Abstract. Despite its limitations, ethanol remains the most commonly used liquid for the preservation of arthropod specimens and their DnA in the field. Arthropod ecology and taxonomy have witnessed a substantial increase in the use of various trapping and molecular methods in the past two decades. However, the methods of collecting and the preservation liquids most widely used in arthropod traps do not properly preserve DNA. Trap-collected specimens are typically of limited utility for molecular studies due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…We tested only the three most commonly used solutions in current biodiversity studies. Recently, Pokluda et al [ 31 ] recommended to use 2% SDS and 100mM EDTA as a cheap, stable and easily transportable alternative to ethanol for preserving specimens and their DNA collected in the field. Its attracting effect has, however, not been tested and while it may be good for DNA it is unknown if community biases (as we found for Renner) might occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We tested only the three most commonly used solutions in current biodiversity studies. Recently, Pokluda et al [ 31 ] recommended to use 2% SDS and 100mM EDTA as a cheap, stable and easily transportable alternative to ethanol for preserving specimens and their DNA collected in the field. Its attracting effect has, however, not been tested and while it may be good for DNA it is unknown if community biases (as we found for Renner) might occur.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that specimens sampled by different sampling solutions highly differ in their effects on DNA quality and genotyping reliability. These studies were, however, either conducted under laboratory conditions [ 5 , 30 ], used only one sampling solution [ 31 ] or used only a short exposition time to avoid evaporation issues when using ethanol [ 32 ] which is not practicable in most biodiversity projects.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Pokluda et al. () have recently shown that 2% SDS and 100 mmol/L EDTA solutions are capable of preserving the DNA of Coleoptera for up to 8 weeks and recommend these for use by entomologists interested in collecting material for barcoding, while Miller et al. () described a method that allowed extraction of DNA from arachnid specimens stored in 70% ethanol for up to 50 years (with varying success depending on the age and body size of the specimen).…”
Section: Choice Of Killing Preservativementioning
confidence: 99%
“…The problem in suggesting a standardized killing preservative is that both the literature on the preservation ability of different preservatives and the techniques to extract DNA from old or degraded specimens is advancing rapidly. For example, Pokluda et al (2014) have recently shown that 2% SDS and 100 mmol/L EDTA solutions are capable of preserving the DNA of Coleoptera for up to 8 weeks and recommend these for use by entomologists interested in collecting material for barcoding, while Miller et al (2013) described a method that allowed extraction of DNA from arachnid specimens stored in 70% ethanol for up to 50 years (with varying success depending on the age and body size of the specimen). The effort of undertaking field studies to investigate how these new preservatives influence capture rates represents a considerable challenge.…”
Section: Choice Of Killing Preservativementioning
confidence: 99%
“…Biodiversi-TEA enables the safe, easy and quick handling and temporary storage of samples, which can later be separated from the filter bags in the lab. Quantities of ethanol that can be transported during flights are strictly regulated (Pokluda et al 2014). Our method allows one to easily discard ethanol from the samples and the SteriBags can be easily stored in stable plastic boxes to avoid damage ( Fig.…”
Section: Discussionmentioning
confidence: 99%